2022
DOI: 10.3389/fmed.2022.989514
|View full text |Cite
|
Sign up to set email alerts
|

Differential retention of adalimumab and etanercept biosimilars compared to originator treatments: Results of a retrospective French multicenter study

Abstract: ObjectivesPrevious studies demonstrated equivalence in terms of efficacy and safety of biosimilars (bsDMARDs) compared to original treatments (boDMARDs) and in switching situations. Less is known about what happens when initiating a bsDMARD in a molecule naïve patient. The objectives of our study were to compare the retention of treatment of subcutaneous boDMARDs and bsDMARDs globally, depending on the disease [rheumatoid arthritis (RA), spondyloarthritis (SpA), or psoriatic arthritis (PsA)], molecule [etanerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 69 publications
1
7
0
Order By: Relevance
“…Our results corroborate those from other real-life studies examining treatment retention in CIRD patients, although results are not completely comparable through to differences in study design. Previous studies that examined RA, PsA or axSpA reported that men have better treatment retention of bDMARDs compared to women 6 , 29 and a better treatment retention has also been demonstrated in patients who had previously been treated with fewer bDMARDs. 6 , 30 33 Although these results were not obtained in a switch setting, they are consistent with our findings.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Our results corroborate those from other real-life studies examining treatment retention in CIRD patients, although results are not completely comparable through to differences in study design. Previous studies that examined RA, PsA or axSpA reported that men have better treatment retention of bDMARDs compared to women 6 , 29 and a better treatment retention has also been demonstrated in patients who had previously been treated with fewer bDMARDs. 6 , 30 33 Although these results were not obtained in a switch setting, they are consistent with our findings.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies that examined RA, PsA or axSpA reported that men have better treatment retention of bDMARDs compared to women 6 , 29 and a better treatment retention has also been demonstrated in patients who had previously been treated with fewer bDMARDs. 6 , 30 33 Although these results were not obtained in a switch setting, they are consistent with our findings. Furthermore, a recent study of patients with CIRD who had undergone medical or non-medical switching from ADA originator to ADA bsDMARD found an increased risk of treatment withdrawal in patients who were treated at baseline with NSAIDs or glucocorticoids.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The RIC-France Network is a database with shared informatic medical records of patients with chronic inflammatory arthritis, and it is used for clinical studies on rheumatic diseases 15 , 16 . Patients are included in the database and data are filled out by their rheumatologists during consultations.…”
Section: Methodsmentioning
confidence: 99%